The influence of the fact of inheritance of property rights of the author under a license agreement on the peculiarities of initiating insolvency (bankruptcy) procedures - O.V. Sushkova (Ученые записки Казанского университета: Серия Гуманитарные науки)
In this paper, the problems associated with determining the status of heirs who are entitled to remuneration under license agreements, as bankruptcy creditors, were analyzed. The theoretical and practical aspects of understanding “intellectual property rights”, as well as the provisions of civil law relating to property and property rights that are part of the inheritance were considered in detail. Theoretical investigation of the mass of the succession formation, if it involves property rights, was performed. In addition, copyright refers to existing jurisprudence, which erroneously interprets the two opposite-polarized concepts of “author’s remuneration” and “remuneration of the author of the result of activities under a license agreement”. Thus, in the case of confirmation of his debt in relation to the rights of heirs under contracts, it is possible to apply to the arbitration court in such a way with initiation of bankruptcy proceedings. It was concluded that the existing legal uncertainty creates an erroneous interpretation and, therefore, application of laws in the current judicial practice. This is due to the fact that the law does not contain a definition of “property rights” in the context of intellectual property rights. The bankruptcy law also does not specify whether it is possible to obtain the status of a bankruptcy creditor in case of having either legally acquired or inherited property rights. In this connection, some corrections were proposed into the current bankruptcy law.